2009
DOI: 10.1002/jmri.21973
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for NSF: A literature review

Abstract: Emerging evidence linking gadolinium-based contrast agents (GBCAs) to nephrogenic systemic fibrosis (NSF) has changed medical practice patterns toward forgoing GBCA-enhanced magnetic resonance imaging (MRI) or substituting other imaging methods, which are potentially less accurate and often radiation-based. This shift has been based on reports of high NSF incidence at sites where a confluence of risk factors occurred in patients with severe renal dysfunction. This review article explores the factors that affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 110 publications
2
93
0
Order By: Relevance
“…This is particularly relevant in patients with compromised renal function or severe allergies and those who cannot be given intravenous, gadolinium-based contrast media. 18 Last, the IVIM method can provide standardized values if the same modeling was used; therefore this method has potential to be used in multicenter clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant in patients with compromised renal function or severe allergies and those who cannot be given intravenous, gadolinium-based contrast media. 18 Last, the IVIM method can provide standardized values if the same modeling was used; therefore this method has potential to be used in multicenter clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in Japan, the reason for the low incidence of NSF cases in Japan may be related to the dosing of Gd-DTPA. In a study by Prince and associates 24 of 182 reported cases of NSF for which data on GBCA dose was available, 90z of patients had received a dose greater than the standard 0.1 mmol/ kg. Therefore, it is possible that administration of high doses of GD-DTPA may be very rare in Japan due to the severe restrictions on dosing by reimbursement guidelines from health insurance providers.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of not involving contrast injection is eliminating the risk of nephrogenic systemic fibrosis (NSF) in patients with compromised kidney function (11). Although principally employed for cerebral blood flow quantification, ASL has begun to see applications outside of the brain, with the kidney being one of the first and most popular sites.…”
mentioning
confidence: 99%